Horses at work [ harnessing power in industrial America - Greene, Ann Norto , 1952- (Harvard University Press, 2008)
New industrial machines and power sources, far from eliminating work animals from nineteenth-century America, required millions of horses to supply the energy necessary for industrial development. Horses were ubiquitous in cities and on farms, providing